Structure of lessons of physical culture in general educational establishments - Vaskov Y.V (Kharkov National Pedagogical University, 2012)
Among the didactic problems of organization of lessons of physical culture the problem of choice of optimum structure of lesson is selected in general educational establishments. The theoretical questions of concept «Structure of lesson» are examined in the article, the questions of plugging in the structure of lesson of the proper stages are probed, components and elements, author determinations over of these concepts are brought. It is well-proven that at choice structure of lesson of physical culture kinds and types of lessons have influence, and types of lessons, and also age of student and teaching stage.